2014
DOI: 10.1007/s11144-014-0763-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodeoxygenation of p-cresol on MoS2: the effect of adding hexadecyl trimethyl ammonium bromide during the catalyst synthesis

Abstract: This study prepared unsupported MoS 2 catalysts by a one-step hydrothermal method using ammonium heptamolybdate and thiocarbamide as materials. The morphology and microstructure of MoS 2 catalysts were changed by adding different amounts of hexadecyl trimethyl ammonium bromide (CTAB). The resultant catalysts were characterized by X-ray diffraction, nitrogen physisorption and transmission electron microscopy. The surface area and pore volume of MoS 2 increased first and then decreased with the addition amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Studies have shown that MoS 2 , which is amorphous and has a short plate length, contains more highly active sulfur vacancies [77] . In the study of the control of slab length, Wang et al [78] . obtained MoS 2 with a shorter slab length and fewer stacked layers by adding an appropriate amount of hexadecyl trimethyl ammonium bromide (CTAB).…”
Section: Design Methods and Effects Of Sulfur Vacancies In The Hdomentioning
confidence: 99%
“…Studies have shown that MoS 2 , which is amorphous and has a short plate length, contains more highly active sulfur vacancies [77] . In the study of the control of slab length, Wang et al [78] . obtained MoS 2 with a shorter slab length and fewer stacked layers by adding an appropriate amount of hexadecyl trimethyl ammonium bromide (CTAB).…”
Section: Design Methods and Effects Of Sulfur Vacancies In The Hdomentioning
confidence: 99%
“…However, the diffraction peaks that correspond to MoS 2 (2θ = 33.4°, 39.5°, 49.5°, 58.6°, and 68.5°) were absent for all studied catalysts. 37 This could be due to the MoS 2 peaks being masked by the alumina peaks, which are in the same region, for instance, 2θ = 33.4° and 39.5°. 37 Another possibility is that the MoS 2 phase was well dispersed on the support and exhibiting low crystallinity.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…37 This could be due to the MoS 2 peaks being masked by the alumina peaks, which are in the same region, for instance, 2θ = 33.4° and 39.5°. 37 Another possibility is that the MoS 2 phase was well dispersed on the support and exhibiting low crystallinity. The metal sulfide phases like NiS, FeS, FeS 2 , and CuS were also not distinguished in the XRD pattern which could be attributed to the relatively low metal loading that is below the XRD detection limit.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…8 In comparison, unsupported catalysts without any support will supply more active components and exhibit better catalytic performance. [9][10][11] The NEBULA TM catalyst family of the Albemarle Catalyst Company is regarded as a representative of unsupported hydroprocessing catalysts, which exhibit at least three times higher HDS activity than traditional g-Al 2 O 3supported CoMo and NiMo catalysts. 12 The unprecedented activity was thought to originate from the abundant metal components, which provide more active sites for the activation of the substrate and H 2 .…”
Section: Introductionmentioning
confidence: 99%